Exploring internet addiction and its associated factors among college students in Western Rajasthan, India: A mixed-methods study - Thota Rajasekhar; Kikkeri Hanumantha Setty Naveen; Pankaja Raghav; Jitender Aneja; Prasanna Thirunavukkarasu; Gitashree Dutta; Srikanth Srinivasan; Prem Prakash Sharma; Manoj Kumar Gupta; Akhil Dhanesh Goel (Indian Journal of Psychiatry)
Background: With near universal use of internet by college students, there is propensity for internet addiction (IA) among them. This study aimed to estimate the prevalence and predict the factors for internet addiction among college students in Jodhpur, Rajasthan, India, and qualitatively explore the factors associated with internet addiction. Materials and Methods: Explanatory sequential (QUAN-QUAL) mixed-methods design was used. A cross-sectional questionnaire-based survey was conducted among three streams of undergraduate colleges (health, engineering, and others). Survey instruments included Young’s internet addiction test (IAT), Pittsburgh Sleep Quality Index (PSQI), and Depression, Anxiety, and Stress Scale-21 (DASS-21) Items. Focus group discussions (FGDs) and in-depth interviews (IDIs) among the students with mild-to-moderate levels of addiction were conducted to understand the reasons for excessive internet use. Results: The prevalence of internet addiction (IA) among the college students was 51% and the rates for mild, moderate, and severe addiction were 31.8%, 18.5%, and 0.7%, respectively. Predictors of IA were male gender, age in years, age of first internet use in years, urban origin, accessing internet at college, mobile internet use, using internet to make online friendship, sleep disturbance, depression, anxiety, and stress. Qualitative study identified five major themes related to situations initiating internet use for nonacademic purpose, content of internet use, triggers for internet overuse/addiction (IA), perceived impact of IA, and measures to overcome IA. Conclusions: Internet addiction was found to be highly prevalent in college students across various streams. Qualitative results provide deeper insights into IA among college students. It is imperative to screen for IA among the students and devise suitable preventive interventions, which can be easily implemented at community level.